Treatment of a Juxtarenal Aneurysm With the Nellix Endovascular Aneurysm Sealing System and Chimney Stent. (August 2014) - Malkawi, Amir H.; de Bruin, Jorg L.; Loftus, Ian M.; Thompson, Matt M.
Purpose: To present treatment of a juxtarenal aneurysm using the Nellix endovascular aneurysm sealing system (EVAS) and a chimney stent. Case Report: A 79-year-old woman was diagnosed with a 6-cm juxtarenal aneurysm. Standard endovascular aneurysm repair was not possible due to lack of an adequate infrarenal landing zone, and poor iliac access and angulated visceral aortic branches precluded a custom-made fenestrated solution. The patient was not a suitable candidate for open surgery due to significant comorbidity, so she underwent successful endovascular aneurysm repair with the Nellix EVAS system and a renal chimney stent. Follow-up imaging at 6 months showed a sealed aneurysm sac and patent renal chimney stent. Conclusion: The Nellix EVAS system obliterates the aneurysm sac using polymer-filled endobags. The ability of the endobags to conform to adjacent structures may offer advantages over conventional endografts when combined with parallel grafts designed to treat juxtarenal aneurysms.